Arthroscopic Bankart Repair Versus Open Latarjet for Recurrent Shoulder Instability in Athletes. Issue 9 (3rd September 2021) - Hurley, Eoghan T.; Davey, Martin S.; Montgomery, Connor; O'Doherty, Ross; Gaafar, Mohamed; Pauzenberger, Leo; Mullett, Hannan
Background: In athletes with recurrent shoulder instability, arthroscopic Bankart repair (ABR) and the open Latarjet procedure (OL) are commonly indicated to restore stability and allow them to return to play (RTP). Purpose: To compare the outcomes of ABR and OL in athletes with recurrent shoulder instability. Study Design: Cohort study; Level of evidence, 3. Methods: We performed a retrospective review of patients with recurrent shoulder instability who underwent ABR and OL and had a minimum 24-month follow-up. Indications for OL over ABR in this population were those considered at high risk for recurrence, including patients with glenohumeral bone loss. The patients were pair-matched in a 1:1 ratio (OL and ABR) by age, sex, sport, and level of preoperative play. We evaluated the rate, level, and timing of RTP, and the Shoulder Instability–Return to Sport after Injury (SIRSI) score between procedures. Additionally we compared the recurrence rate, visual analog scale (VAS) pain score, Subjective Shoulder Value (SSV), Rowe score, satisfaction, and whether patients would undergo the same surgery again. Results: Participants included 62 athletes who underwent ABR and 62 who underwent OL, with a mean follow-up of 47.7 months. There was no significant difference between ABR and OL in rate of RTP, return to preinjury level, time to return, SIRSI score, VAS score, SSV, or patient satisfaction. OL resulted in a significantly lower recurrence rate (1.6% vs 16.1% for ABR; P = .009) and a significantly higher Rowe score (mean ± SD, 90.5 ± 12.2 vs 82.2 ± 20.8 for ABR; P = .008). In collision athletes, there was no significant difference between ABR and OL regarding RTP rate (89.1% vs 94.5%; P = .489) or SIRSI score (70.4 ± 24.8 vs 73.8 ± 19.6; P = .426), but OL resulted in a lower recurrence rate (14.5% vs 1.8%; P = .031). Conclusion: ABR and OL resulted in excellent clinical outcomes, with high rates of RTP in athletes. However, lower recurrence rates were seen with OL.